Detection of co-infection by Candidatus phytoplasma australasiaticum and tomato leaf curl New Delhi virus in sesame in Telangana state, India - Bhaskar, B; Anitha, K; Channakeshava, C; Pavithra, B S; Parameswari, B; Sivaraj, N; Reddy, M Krishna (Indian Journal of Plant Protection, 2025)
Sesame is a major oilseed crop cultivated in India. One accession of sesame in germplasm evaluation plots at ICAR-NBPGR Regional Station, Hyderabad, exhibited both phyllody and leaf curl symptoms, and it was suspected to be due to the infection of both phytoplasma and begomovirus. Then, the genomic DNA of the sample was examined by PCR testing with P1/P7-specific primers and 971F/2142R primers to amplify the phytoplasma 16S-23S rRNA gene and the begomovirus DNA-B genome, respectively. The results of the amplification revealed that the sample was positive for both phytoplasma and begomovirus. The sequence of the 16S–23S rRNA gene and its phylogeny with other phytoplasma strains identified the existence of Candidatus Phytoplasma australasiaticum. In addition, the sequence of the begomovirus DNA-B genome and its phylogenetic investigations identified the tomato leaf curl New Delhi virus (ToLCNDV). Thus, the findings of the present study detected a co- infection of Ca. P. australasiaticum and ToLCNDV with sesame phyllody and leaf curl disease.